ANALISIS FAKTOR YANG MEMPENGARUHI KETERLAMBATAN PENYAMPAIAN LAPORAN KEUANGAN PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2011-2013 - Erin Juniati; Amir Hasan; AL Azhar A ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aims to determine emprical prove to influence complexcity, firm size, profitabiliy, and solvency toward audit delay. The Population of this study in the miningcompanies listed in Indonesian Stock Exchange 2011-2013 with the purposive sampling technique and total sample 38 company, with three years observasion . The methode use analysis logistic regression by Statistical Product Service Solution (SPSS) version 20 as the software for processing the data.The significant complexcity to audi delay is 0,03%, significant firm size to audit delay is 0,04%, significant profitability to audit delay is 0,3% and significant solvency to audit delay is 0,24%. The result shows that the complexcity (KOMP) and firm size(UP) significantly influence to audit delay. Profitability(ROE) and solvency(TDTA)has no significant impact onAudit delay.Keywords : Audit delay, complexcity, firm size, profitabiliy, and solvency.